Experimental Study of Soil Compaction with Proctor Standard Test Equipment - Fatkunada, Nur Addin; Candra, Agata Iwan; Setiawan, Dodi (Universitas Negeri Padang, 2024)
Soil is the surface layer of the earth which consists of minerals, organic materials, air, living things. Clay soil is one type of soil that is important in determining the bearing capacity of subgrade required for construction. The bearing capacity of the soil is obtained by compacting it, using the TS-365 Automatic Standard Proctor. Soil compaction is the process of removing air from the pores of the soil, and is effective for improving soil properties in order to increase the density (density) of the soil so that shear strength increases, soil settlement decreases, and soil permeability decreases. The standard proctor test uses 5 separate soil samples weighing 2 kg, with a mixture of 16%, 19%, 22%, 25% and 28% air respectively. The test results show that the soil obtained from the Pojok sub-district area. Mojoroto, East Java obtained the results of soil compaction data using a standard proctor test, it was obtained that the optimum dry volume weight of the soil was 1,630 gr/cm3 and the optimum water content was 32%. So that the results of soil testing in the laboratory can be used as a reference for controlling soil compaction in construction.